2018
DOI: 10.1002/anie.201713357
|View full text |Cite
|
Sign up to set email alerts
|

Transient‐Ligand‐Enabled ortho‐Arylation of Five‐Membered Heterocycles: Facile Access to Mechanochromic Materials

Abstract: Reported herein is the first example of a direct arylation of heteroarenes by a transient-ligand-directed strategy without the need to construct and deconstruct the directing group. A wide range of heteroarenes undergoes the coupling with diverse aryl iodides to assemble a large library of highly selective and functionalized 3-arylthiophene-2-carbaldehydes. This route provides an opportunity to rapidly access new mechanofluorochromic materials. Moreover, a novel strategy for mechanochromic luminogens with chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 41 publications
0
39
0
1
Order By: Relevance
“…This strategy provided an opportunity to rapidly build up new mechanofluochromic materials. Through facile functional group modifications, we realized a novel synthetic strategy for mechanochromic luminogens with chromism trends of red‐ and blueshift based on TPA (triphenylamine)‐containing β‐aryl‐substituted five‐membered heterocyclic carbonyl compounds (Scheme a) . The proposed reaction mechanism is shown in Scheme b. Condensation of 1 with L19 forms the imine intermediate I , which coordinates with palladium species to afford the corresponding six‐membered cyclic palladium complex II .…”
Section: Reversible Covalent Bonding For Transition Metal‐catalyzed Cmentioning
confidence: 99%
See 2 more Smart Citations
“…This strategy provided an opportunity to rapidly build up new mechanofluochromic materials. Through facile functional group modifications, we realized a novel synthetic strategy for mechanochromic luminogens with chromism trends of red‐ and blueshift based on TPA (triphenylamine)‐containing β‐aryl‐substituted five‐membered heterocyclic carbonyl compounds (Scheme a) . The proposed reaction mechanism is shown in Scheme b. Condensation of 1 with L19 forms the imine intermediate I , which coordinates with palladium species to afford the corresponding six‐membered cyclic palladium complex II .…”
Section: Reversible Covalent Bonding For Transition Metal‐catalyzed Cmentioning
confidence: 99%
“…[30b] In 2018, our group demonstrated the palladium-catalyzed direct arylation of heterocyclic aromatic ketones by at ransientligand-directed strategy.W ef ound that either 3-amino-3-methylbutanoic acid (L19)o rg lycine (L21)c ould be used as at ransient ligand to promote the direct C(sp 2 )ÀHf unctionalization (Scheme 14 c) . [19] Very recently,L in, Wei, and co-workersa lso demonstrated that ad irect arylation of aromatic ketonesc ould be carried out through Pd-catalyzed inert C(sp 2 )ÀHb ond functionalization with 2-amino-N-isopropyl acetamide (L28)a sanovel transient…”
Section: C(sp 3 )àHfunctionalization Of Aliphatic Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation
“…Substoichiometric TDG reagents first reversibly link to substrates forming temporary directing groups, facilitating substrates to undergo cyclometalations and C−H functionalizations, and then readily dissociate from the functionalized products without any extra prior and after operations . This TDG strategy has been applied to C( sp 2 )−H functionalization of benzaldehydes, diphenyls, ferrocene, aromatic ketones and five‐membered heterocycles . Recently, this strategy was also used to perform C( sp 3 )−H functionalizations of aldehydes, ketones and amines in moderate to good yields.…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 99%
“…[2] This TDG strategy has been applied to C(sp 2 )À H functionalization of benzaldehydes, [3] diphenyls, [4] ferrocene, [5] aromatic ketones [6] and fivemembered heterocycles. [7] Recently, this strategy was also used to perform C(sp 3 )À H functionalizations of aldehydes, [8] ketones [9] and amines [10] in moderate to good yields.…”
mentioning
confidence: 99%